0174 Preliminary results of shift work and cardiovascular risk factors: analysing baseline data of a prospective night shift worker cohort in Shenzhen, China. (23rd June 2014) - Tsc, Shelly Lap Ah; Wang, Feng; Zhang, Liuzhuo; Zhang, Yanfang; Zhang, Bo; He, Yonghua; Xie, Shaohua; Li, Mengjie; Li, Zhimin; Yu, Ignatius Tak-sun
Abstract : Objectives: The incidences of cardiovascular diseases (CVD), diabetes mellitus and metabolic syndrome increase rapidly in China, while the prevalence of night shift work is also increasing. This study aims to investigate the relationship between night shift work and CVD risk factors by analysing the baseline data of a prospective cohort study. Method: We are establishing a prospective night shift worker cohort in Shenzhen, China. More than 10 000 workers will be recruited and followed up. Currently, we have recruited more than 4000 workers but most questionnaires have not yet been input. A standardised questionnaire is used to collect information on lifetime night shift work, light at night, occupational hazards, sleep disorders, etc. Fasting blood and spot urine samples are also collected for further usage. CVD risk factors include hypertension, diabetes, overweight and dyslipidemia etc. All participants will have the annual or biennial occupational physical examination. Results: We reported data from a manufacturing company dealing with welding and shipment. We obtained 131 day workers and 370 shift workers with a response rate of 95%. The shift workers are significantly younger than day workers. The smoking and alcohol drinking status are comparable in two groups. The presence of number of CVD risk factors positively relate to the years of shift work after adjusting for age and other confounding factors. Conclusions: These preliminary results suggest long-term night shift work may increase CVD risk factors, while these will be updated in the conference. [National Natural Science Foundation of China (Project number 81273172 and 81372964), Shelly@cuhk.edu.hk (Lap Ah Tse)]